Synchronous neoplasms in a paediatric patient - Dembowska, Aleksandra; Dubaj, Maciej; Bigosiński, Karol; Raniewicz, Mateusz; Mitura-Lesiuk, Małgorzata (Pediatria Polska - Polish Journal of Paediatrics, 2024)
Cancer is the second leading cause of death in the paediatric population after injuries. 3–10% of them are multiple primary malignant neoplasms, which are a huge problem both in diagnosis and treatment. We present a case of a boy, nearly 2 years old, with synchronous coexistence of T-cell acute lymphoblastic leukaemia and Langerhans cell histiocytosis. During the M AIEOP BFM ALL 2017 Protocol, the patient suffered an injury to the right elbow joint. Despite the limb being provided with a plaster cast and orthopaedic intervention, local improvement was not achieved. The obtained result of the histopathological examination revealed a disseminated aggressive form of histiocytosis affecting the skeletal system and lungs. In the presence of non-specific symptoms for the diagnosed cancer, one should be vigilant and suspect the coexistence of another proliferative process, which may cause no improvement despite proper therapeutic management.